The Fanqala (Dialectical ‘Fa-in Qeela… Qultu’ Style) in Imam al-Mawardi’s Al-Hawi: An Applied Study on Issues of the Intention of Fasting. - Zahraa Saad Abdul Razzaq, (Islamic Sciences Journal, 2025)
The research examines the jurisprudential Fanqala method of Imam Al-Mawardi in his book Al-Hawi—an applied study on issues concerning the intention of fasting—by presenting his personal and scholarly biography, explaining the jurisprudential issues regarding the intention of fasting, the method of questioning, points of dispute, and Al-Mawardi’s Fanqala, presenting the opinions of the four well-known jurists, discussing the evidence from the Qur’an and Sunnah, and demonstrating the evidential reasoning and giving the preferred view.